A new protocol for the simultaneous flow cytometric analysis of cytotoxicity and immunotoxicity on zebra mussel (Dreissena polymorpha) hemocytes. Issue 98 (March 2020) - Barjhoux, Iris; Rioult, Damien; Geffard, Alain; Palos Ladeiro, Melissa
Abstract: Immunotoxicity analysis receives a strong interest in environmental a priori and a posteriori risk assessment procedures considering the direct involvement of the immune system in the health status of organisms, populations and thus ecosystems. The freshwater mussel Dreissena polymorpha is an invasive species widely used in ecotoxicology studies and biomonitoring surveys to evaluate the impacts of contaminants on aquatic fauna. Bivalve hemocytes are the immunocompetent cells circulating in the open circulatory system of the organism. However, there is nowadays no consensus on a protocol to evaluate the immunocompetent state of this particular cell type using flow cytometry. Wild species such as D. polymorpha present several technical barriers complicating their analyze including (i) the quality and the purity of the hemolymph sample, (ii) the controversial characterization of hemocyte subpopulations and their diversity, (iii) the quantity of biological material, and (iv) the high inter-individual variability of hemocyte responses. The present work proposes several technical and analytical improvements to control the above-mentioned issues. The inclusion of sedimentation and cell detachment steps in the pre-analytical phase of the protocol substantially ameliorate the quality of the hemolymph sample as well as the accuracy of the cytometric measurements, by selecting the analyzed cells on their adhesion ability and by increasing the concentration of the analyzed events. The development of an effective triple-labeling procedure including the cellular probe Hoechst® 33342, the membrane impermeant dye propidium iodide and yellow-green fluorescent microspheres allowed the simultaneous analysis of cytotoxicity and phagocytosis activity in hemocytes. It also significantly enhanced the accuracy of hemocyte endpoint measurements by eliminating non-target events from the analysis and allowing relevant gating strategies. Finally, the use of pooled samples of hemolymph noticeably reduced inter-sample variability while providing more plasticity in the experimental design and improving the discriminating potency between treatments. The developed protocol is suitable for ex vivo exposure of hemocyte in a chemical/environmental toxicity assessment as well as for in vivo exposure in the laboratory or in situ biomonitoring surveys with few adaptations. Graphical abstract: Image 1 Highlights: Cell detachment enhances the representativity of the analyzed cell population. The triple labeling procedure improves the accuracy of measured endpoints. Hemocyte adhesion ability is used to select functional cells for further analysis. Hemocyte adhesion is a key property to consider before flow analyses.